PEMODELAN IPM DI KAWASAN TIMUR INDONESIA MENGGUNAKAN MULTIVARIATE ADAPTIVE REGRESSION SPLINE (MARS) - Insany, Annisa Nur; Nur?eni, Nur?eni; Fajri, Mohammad (Natural Science: Journal of Science and Technology, 2019)
Human Development Index (HDI) is an important issue in designing  and strategizing of sustainable development. Multivariate Adaptive Regression Spline (MARS) is a regression approach that produces models with continous character on knots. MARS models are determined based on trial and error for a combination of basis function (BF), maximum interaction (MI), and minimum observation (MO). The determination of knots is based on the minimum Generalized Cross Validation (GCV) value. The results of this study are the combination value of BF = 52, MI = 3, and MO = 2 with a minimum GCV of 0,00049. The factors that influence HDI are average school length (X2) per capita expenditure (X4), life expactancy (X3), persentage of poor woman aged 15-49 who use the birth control tool (X5).